THE IMPACT OF USING THE QRIS FEATURE ON CUSTOMER TRANSACTIONS - Hendrian Yonata (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Quick Response Code Indonesian Standard (QRIS) is the most efficient instant payment method which is a collaboration product between Bank Indonesia and the Indonesian Payment System Association (ASPI). Non- cash payments in the digital era have made Bank Indonesia innovate non-cash payment systems by promoting and socializing to the public about the Quick Response Code Indonesia Standard (QRIS). The presence of QRIS can improve non-cash payment system services efficiently. QRIS has become an increasingly common technology used in electronic payments in Indonesia, and this research aims to understand how QRIS affects transaction patterns, customer convenience. Consumers are the parties who encourage the implementation of QRIS in transactions. A consumer is someone who buys goods or uses services. The public's enthusiasm for using QRIS is a momentum that can be used to accelerate the acceleration of QRIS. There is high interest from the Indonesian people, the majority of whom consist of the millennial generation, to be able to make digital payment transactions easily, quickly and safely. The many conveniences provided by QRIS make people carry out completely digital transactions. Of course there are advantages and disadvantages to using the QRIS payment method.